Students' perception on the use of Google Translate in learning Pronunciation - Uswatun Khasanah; A.Hilal Madjdi; Nuraeningsih Nuraeningsih (Borneo Educational Journal (Borju), 2022)
Since the Covid-19 pandemic that occurred in Indonesia, teaching and learning activities must be carried out online. Therefore, to improve students’ pronunciation skills, the teacher suggests to students to use Google Translate Application as media to learn pronunciation independently. Google Translate is an application that has various features, one of them is the pronunciation feature that can convert sound into text. This feature can be used by students’ to practice pronunciation so that it can train students’ ability to pronounce difficult words. The aim of this research is to describe the students’ perceptions of using Google Translate Application and to describe the obstacles do students find using Google Translate Application as media in learning pronunciation. This research used descriptive qualitative research design. The participants of this research is 15 students of the tenth grade an Islamic public senior high school in Kudus, Indonesia. The data was collected by distributing a questionnaire to the respondents. The result of this research shows the students’ perception on using Google Translate Application as media in learning pronunciation was positive, because students can learn practically and independently. While the obstacles that students found when learning pronunciation using Google Translate were that Google Translate often had errors, could not be used offline, took a long time to load, and had low accuracy. Therefore, to help students improve their pronunciation ability, students’ can use Google Translate Application as learning media. To minimize obstacles when using Google Translate Application, it is recommended to use Wi-Fi, so that the connection is good so that loading can be faster and reduce errors.